If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y + 2x = 14 Reorder the terms: 2x + y = 14 Solving 2x + y = 14 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1y' to each side of the equation. 2x + y + -1y = 14 + -1y Combine like terms: y + -1y = 0 2x + 0 = 14 + -1y 2x = 14 + -1y Divide each side by '2'. x = 7 + -0.5y Simplifying x = 7 + -0.5y
| 4a^2-3a-24=0 | | sin^2x=3cos^2x | | 75(2)= | | 2w+4x-11y+7w+10x+5y= | | 10x(0)=x | | 2/5+y-8=11 | | 2(x-9)=-15.4 | | -4v^2+32v=64 | | 9y-4y+20=40 | | 752/2= | | (6d+5)-(-2-3d)= | | 4*(10*-10)= | | 6(3m-5)=66 | | 7x-10+5x+7=-20-7 | | 21+18m=183 | | 4a^2-3a-16=0 | | x/2+8= | | 7(x-4)=-42 | | -[z-3y-(3x-z-2y)+3z+2y]-x= | | 9(a+1)=79.2 | | (16-2x)=10x | | 74=8c-2 | | -10=-5(7-5a) | | 21(24)= | | 12*0.5h=18*2h | | (9x+10)+(6x-4)= | | 9+7y=51 | | 9e-4=78.8 | | 9(2x+4)+7x= | | 8x^4+2x=0 | | 22-43=4(x-1)-4 | | h=-16(t)(t-9) |